Outbound Activities to Improve the Social Skills of Group B Children at Kingdergarten Kartika Siliwangi 39 Serang - Lesiani, Lesi; Rahmawati, Sita; Ariyani Kangiden, Farida (LPPM Universitas Primagraha, 2023)
This research aims to improve children's social skills through outbound activities. The method used is classroom action research consisting of two cycles. In cycle I there were 8 actions and in cycle II there were 2 actions, with a success criterion of 76%. The data collection techniques are through observation, field notes, interview notes and documentation. Data analysis uses data reduction, data presentation, and conclusions. The results showed that the social skills of children aged 5-6 years improved in each cycle. In pre-action it was 26.4%, cycle I was 47.1% and cycle II was 85.1% and exceeded the success criteria for the targeted indicators. Based on the results of the data that has been obtained, it can be concluded that implementing outbound activities can improve the social skills of group B children at Kindergarten Kartika Siliwangi 39 Serang.